Tamong To Pusaka Weeg integrating the Obu Manuvu Pusaka philosophy in the systems approach for Erosion Management of the Panigan-Tamugan Watershed - Tupaz, Jyllean Marye S.
The Obu Manuvu have stood for centuries as vanguards for the Panigan-Tamugan Watershed (PTW) in Davao City, the thriving land of their ancestors and the living manifestation of their history. Their indigenous ecological knowledge has maintained these rivers at the highest quality for potable freshwater, Class AA. However, its health is threatened by river degradation from deforested slopes, agricultural wastes, and illegal land uses while its stewards find themselves in conflict with other stakeholders in demand of resources amidst the region’s growing population. This thesis aims to assert the value of Obu Manuvu ethnoecology and apply their “Pusaka” philosophy in watershed conservation through the expanded integration of their knowledge in the creation of a watershed management approach. The research design is grounded in three theories led by a Systems Approach, namely Landscape Ethnoecological Classification, Source-Sink, and Complex Adaptive Systems. The methodology is guided by Obu Manuvu insights through focus group discussions, mapping workshops, and field documentation, which were then analyzed through thematic text coding, folk ecotope maps, and landscape assessments to determine the best planning scenario to develop into a culture-based approach. Landscape plans and policy recommendations were designed to visualize the approach in benefiting the conservation of water resource quality in Panigan-Tamugan. It is hoped that the articulation of the Obu Manuvu landscape stewardship as a watershed management approach will improve the integrity of the PTW and represent the essentiality of indigenous perspectives on nature conservation.